Punching bag and resistance band training: How does it affect the accuracy of Gyaku Tsuki punches in terms of arm muscle strength? - Adriani, Desi; Rismayanthi, Cerika; Ciptadi, Zaniar Dwi Prihatin; Jurek, Joanna Michalina (Tanjungpura Journal of Coaching Research, 2025)
Background and Study Aim. Punch accuracy is an important aspect of karate, especially in the Gyaku Tsuki technique which demands precision and optimal strength. Various training methods have been developed to improve punch accuracy, including punching bag and resistance band training. This study aims to analyze the effect of punching bag and resistance band training on the accuracy of Gyaku Tsuki punches in karate athletes, considering arm muscle strength factors.Material and Methods. The research method used was an experiment with a 2x2 factorial design. The research subjects consisted of karate athletes who were divided into four groups based on the type of training and the level of arm muscle strength (high and low) there were 60 athletes practicing at Dojo Inkai. Measurement of punching accuracy was carried out using the targeted punching test and video analysis. Furthermore, the analysis was assisted by the SPSS 26 application.Results. The Two-Way ANOVA results showed a significant difference (p < 0.05) between punching bag and resistance band training on Gyaku Tsuki accuracy. Athletes with high arm muscle strength benefited more from punching bag training, while no significant difference was found between the methods for those with low arm strength. An interaction effect (p < 0.05) indicated that training effectiveness depends on athletes' physical characteristics.Conclusions. These findings provide important implications for coaches and athletes in developing more effective training programs. The punching bag exercise is recommended for athletes with high arm muscle strength, while resistance bands can be used as an alternative to improve stability and muscle endurance. This research also opens opportunities for further studies related to other training variations in improving the accuracy of punching techniques in karate.